Pengaruh Profitabilitas, Leverage, Earnings Per Share, dan Tax Planning Terhadap Return Saham - Yoewono, Harsono (Owner : Riset dan Jurnal Akuntansi, 2024)
The goal of this study was to examine how factors like as profitability, leverage, earnings per share, and tax strategy affect the return on investment for shareholders. Variable earnings per share proxied by eps. The ratio of debt to equity serves as a proxy for the leverage variable. Profitability variable is proxied by return on asset. And tax planning variable is proxied by effective tax rate. Share return was considered as important by investor and company because it describes the financial performances of company. This study looked at many industries during the course of the years 2016-2022. Purposive sampling was used to pick the sample, and a total of 10 businesses were included. The multiple regression approach was used to examine the secondary data used in this study. This study found that profits per share did not influence share return, and leverage had a negative impact on stock returns. A negative and negligible impact on stock returns, profitability didn’t effect share return, and tax planning didn’t effect share return. Earnings per share, leverage, profitability, and tax planning simultaneously influence stock returns.